Krosno Odrzańskie jako strategiczny punkt obrony zachodnich rubieży Polski Średniowiecznej = Krosno Odrzańskie as a strategic defence point of Polish medieval western frontiers - Knyspel-Kopeć, Renata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The earliest mention of Krosno preserved in writing, dated 1005, speaks of a great army which crossed a bridgehead on the bank of the Odra river near Krosno, in an attempt to subdue it. From the description of the chronicler, Bishop Thietmar of Marseburg, who witnessed those events, we learn that the king Bolesław Chrobry, having fortified the shore of the Odra river, settled with his large army near Krosno, making it difficult for the German king Henry to get across.
Keywords: Krosno Odrzańskie; historia; średniowiecze